The graveyard book. - Russell, P. Craig (Bloomberry Publishing, 2014)
The concluding volume of the graphic novel adaptation of the book about a boy, raised by the inhabitants of the local graveyard who rally to protect him from a league of villains named Jack that seeks to destroy him.